RETAIL SERVICE QUALITY AND BEHAVIOURAL INTENTIONS: AN EMPIRICAL APPLICATION OF THE RETAIL SERVICE QUALITY SCALE IN NORTHERN CYPRUS - Nadiri, Halil; Tumer, Mustafa (Technical Univ Liberec, 2009)
In the highly competitive retail sector, the provision and measurement of superior retail service quality is crucial for gaining a sustainable competitive advantage. Service quality is an important strategic weapon in retail contexts, particularly in developing defensive marketing strategies. The measurement of service quality in a retail setting is somewhat different from the measurement of service quality in other pure service settings. The most widely known and discussed scale for measuring service quality -SERVQUAL- has not been successfully adapted to and validated in a retail store environment. The retail service quality scale' (RSQS) [1] has been validated in the USA, Hong Kong, and Korea, but not in other cultural settings. Only a limited number of studies have attempted to measure service quality in retail settings, so there is a significant gap in the literature regarding this area of research. The present study addresses this gap by applying the RSQS among 648 customers of a large chain of retail stores in Northern Cyprus. The study also proposes and tests two hypotheses regarding the relationship between retail service and customers' behavioural intentions. The results confirm the applicability of the original five dimensions of the RSQS in the setting of Northern Cyprus. Retail service quality is shown to be positively related to behavioural intentions (intention to repurchase and intention to recommend). Multi-regression analyses reveal that the dimensions of physical aspects', problem solving', and reliability' have the greatest impact on customers' behavioural intentions. The study also analyses the relationship between certain demographic characteristics and perceptions of service quality. The results, managerial implications, and suggestions for future research are discussed in detail.
Keywords: retailing; service quality; perceptions; Northern Cyprus